CARNOY’S SOLUTION AS A SURGICAL MEDICAMENT IN THE TREATMENT OF KERATOCYSTIC ODONTOGENIC TUMOUR - DR. MADHULAXMI. M; DR. P.U. ABDUL WAHAB (International Journal of Pharma and Bio Sciences, 2014)
Carnoy’s solution was first used as a medicament in surgery by Cutler and Zollinger in 1933. The reformulated carnoy’s solution without chloroform is accepted because exposure to chloroform has been associated with cancer and reproductive toxicity. It is assumed that carnoy’s solution eradicates epithelial rests from the cyst wall and reduces the rate of recurrence. In the world health organization (WHO) classification of head and neck tumours from 2005, odontogenic keratocyst was reclassified and renamed to keratocystic odontogenic tumour (KCOT). Rate of recurrence was reduced when carnoy’s solution was used as an adjunct therapy after the enucleation of keratocystic odontogenic tumour.